Development of abbreviated measures to assess patient trust in a physician, a health insurer, and the medical profession - Trachtenberg Felicia; Dugan Elizabeth; Hall Mark A (BMC, 2005)
Abstract Background Despite the recent proliferation in research on patient trust, it is seldom a primary outcome, and is often a peripheral area of interest. The length of our original scales to measure trust may limit their use because of the practical needs to minimize both respondent burden and research cost. The objective of this study was to develop three abbreviated scales to measure trust in: (1) a physician, (2) a health insurer, and (3) the medical profession. Methods Data from two samples were used. The first was a telephone survey of English-speaking adults in the United States (N = 1117) and the second was a telephone survey of English-speaking adults residing in North Carolina who were members of a health maintenance organization (N = 1024). Data were analyzed to examine data completeness, scaling assumptions, internal consistency properties, and factor structure. Results Abbreviated measures (5-items) were developed for each of the three scales. Cronbach's alpha was 0.87 for trust in a physician (test-retest reliability = 0.71), 0.84 for trust in a health insurer (test-retest reliability = 0.73), and 0.77 for trust in the medical profession. Conclusion Assessment of data completeness, scale score dispersion characteristics, reliability and validity test results all provide evidence for the soundness of the abbreviated 5-item scales.